PI controller for photovoltaic-fed novel multilevel inverter topologies - Dhandapani Karthikeyan; Simran Rajiv Khiani; Albert Alice Hepzibah; Uthayakumar Jothilingam; Ravindran Ramkumar; Arumbu Venkadasamy Prathaban; Krishnasamy Vijayakumar (Institute of Advanced Engineering and Science, 2023)
This research describes the analysis and design of a unique 7-level and 9-level multi-level inverter topology with fewer DC power supplies and power switches, and a comparison using pulse width modulation (PWM). Comparisons of 7-level and 9-level multi-level inverters that analyze characteristics using optimal nearest level modulation (ONLM) technology are made using various PWM approaches such as nearest level modulation (NLM) technique, phase disposition (PD), phase opposition disposition (POD), and alternate phase opposition disposition (APOD). The output is evaluated based on a high Vrms, low total harmonic distortion (THD) harmonic profile. The controller is based on artificial intelligence (AI) and machine learning (ML) techniques. ONLM techniques are used to measure the voltage harmonics of the full load, several DC offset values are used. The control technology provided is validated using MATLAB/Simulink simulation tools and laboratory-based experimental testing.